Pengaruh Gaya Kepemimpinan Transformasional terhadap Kepuasan Bekerja di Departemen Front Office Hotel Padma Bandung - Raynaldi, Muhammad Ryky; Nurazizah, Ghoitsa Rohmah (Tourism and Hospitality Essentials Journal, 2024)
Leadership style in a company is important, because it relates to the relationship between the manager and his subordinates in order to create a good work environment and have good quality work. In this study, the aim was to analyze the effect of transformational leadership style on job satisfaction in the front office department of Padma Hotel Bandung. This study has an independent variable, namely transformational leadership (X), which has sub-variables, namely Individualized Consideration (X1), Intellectual Stimulation (X2), Intellectual Stimulation (X3) and Idealized Influence (X4). Meanwhile for the dependent variable of this research is job satisfaction (Y). In this study, the research method used is descriptive research with a quantitative approach. This study collected data from 38 front office employees at Padma Hotel Bandung which were collected through a questionnaire. Sampling using saturated sampling. The IBM SPSS 26 for Windows software application is used in this study to process data. From the results of data processing, it can be seen that Padma Hotel Bandung's front office department employees feel satisfied with the transformational leadership style possessed by their manager. Furthermore, the transformational leadership style has an influence value of 73.1% on employee job satisfaction. The Y variable value as a whole is 997 with a percentage of 85.7% and the indicator with the highest score in the job satisfaction variable is the job indicator with a percentage of 88.9% and the lowest indicator value is salary with a percentage of 78.4%.